LEGAL ANALYSIS OF PARTNERSHIP AGREEMENTS BETWEEN OJEK COMPANIES ONLINE WITH MOTORCYCLE TAXI DRIVER ONLINE - Nandito Kelvianto Wibowo; Arikha Saputra (Jurnal Meta-Yuridis, 2023)
online motorcycle taxi is one of the businesses created from technological developments. Online motorcycle taxis themselves use a partnership agreement as an agreement between online motorcycle taxi companies and online motorcycle taxi drivers. In the partnership agreement between the MAXIM online motorcycle taxi company and MAXIM online motorcycle taxi drivers, the agreement made is a standard agreement which does not give the driver any other choice, which is in conflict with the terms of the agreement. Therefore, this study aims to look at the course of the partnership between the MAXIM online motorcycle taxi company and MAXIM online motorcycle taxi drivers and the legal protection provided in the MAXIM partnership agreement using normative juridical research methods with descriptive analytical specifications.The results of the research on the partnership agreement between online motorcycle taxi companies and online motorcycle taxi drivers are that MAXIM as the service provider company has previously made a partnership agreement and the agreement is a standard agreement where drivers cannot do anything in the contents of the agreement, in other words, they can only accept if want to be part of the MAXIM online motorcycle taxi driver partner where this is not in accordance with the terms of the legal agreement. The legal protection that MAXIM online motorcycle taxi drivers get is preventive legal protection and repressive legal protection. preventive legal protection is legal protection provided by the Indonesian government, while repressive legal protection is protection provided by MAXIM